Developing a Textbook of Creative Poetry Writing Based on Local Wisdom Problem Based Learning - Yuyun Safitri; Sarwiji Suwandi; Herman Waluyo; M. Soediro Satoto (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2018)
The purpose of this article is to describe: (1) Condition textbook of creative writing poetry which is used in learning “Creative Writing Poetry” for the student of Indonesian Language and Literature Education in University of West Kalimantan. (2) Needs of the Student and Lecturer of Indonesian Language and Literature Education Study Program in West Kalimantan University in developing textbook if creative writing poetry based on local wisdom. Methodology which is used is research and development. Conclusions of the research result are as follow: (1) condition of the creative writing textbook which is used in earning creative writing poetry is inadequate, the detail of the book is less clear and less appropriate to the condition of the student. The poetry which is used are less attention to the face of poetry (typography), diction, imagination, concrete word, language style, rhyme/rhythm, theme/mean, feeling, tone, mandate/purpose/mean, and less attention to local wisdom. (2) Student and lecturer need a special book about creative writing poetry based on local wisdom which contains the text of poetry based on local wisdom and supporting illustration image, and also the evaluation sheet.